Fermentation Tecniques and Applications of Bacterial Cellulose: a Review (2012)
Bacterial cellulose is a polymer obtained by fermentation with microorganisms from Acetobacter, Rhizobium, Agrobacterium and Sarcina genera. Amongthem, Acetobacter xylinum is the most eﬃcient specie. This polymer has the same chemical composition of plant cellulose, but its conformation and physicochemical properties are diﬀerent, making it attractive for several applications, especially in the areas of food, separation processes, catalysis and health, due to its biocompatibility. However, the main problem is the production in mass that is constrained by low yield. It is therefore necessary to develop some alternatives. This paper presents a review about synthesis, production, properties and principal applications of bacterial cellulose, as well as some alternatives to reduce the diﬃculties for process scaling.